Avaliação da sensibilidade ao mutágeno peróxido de hidrogênio em pacientes cronicamente infectados pelo vírus da Hepatite C - Braga, Lilian Nayara (2016)
The mutagen sensitivity is considered an indirect measure of DNA repair efficiency. Although it is considered predominantly an heritable characteristic, many environmental factors may influence the individual ability to repair DNA damage. The chronic infection by hepatitis C virus (HCV) has been related with increased frequency of oxidative lesions and DNA damage in both hepatocytes and lymphocytes, besides it is associated with the development of hepatocellular carcinoma and lymphoproliferative diseases. These evidences suggest that the chronic infection by HCV may results in decreasinf of DNA damage repair, contributing to accumulation of mutations in the infected subjects. In this study, we investigated if lymphocytes of patients chronically infected with HCV (HCV patients) are sensitive to the hydrogen peroxide using mutagen sensitivity test and the DNA repair kinetics assay. Twenty-three HCV patients and 39 healthy controls were investigated regarding the sensitivity to hydrogen peroxide using the micronucleus (MN) test. The levels of oxidative DNA damage were accessed at diferent times (0, 30, 60 and 120 minutes) after the treatment with hydrogen peroxide using the comet assay modified with hOGG1 enzyme. There are no differences between age (42.82±13.35; 38.38±12.11; p = 0.18), sex (p=0.43) or smoke habit (p=0.5) in both groups. The daily consumption of alcohol ranged from 0 to 6g to the HCV patients and 0 to 10g to the control group. The basal number of MN was similar (p=0.30) between HCV patients (12.08±5.41) and controls (10.56±4.49). The DNA net damage (number of MN in cells treated with hydrogen peroxide- number of MN in cells non-treated with hydrogen peroxide) was 2.3x higher in HCV patients cells (10.34±14.07) in comparison to the controls (4.59±3.29, p=0,05). When all subjects were classified in sensitive and non- sensitive to hydrogen peroxide according a cut-off point (50% percentil), we observed na increased frequency of HCV patients (59.1%) between the sensitive subjects in comparison to the controls (30.8%). The DNA repair kynetics analysis demonstrated that the cells of control group totally recovered the oxidative DNA lesions at 120 minutes after the H2O2 treatment, whereas the HCV patients cells did not showed increase in levels of oxidative DNA damage after the treatment. These results suggest that HCV infection contributes to peroxide hydrogen sensitvity phenotype in patients with chronic hepatits C.